Identifying causative elements within structural variants associated with developmental disorders - Boulding, H (2013)
It has been well established that copy number variation contributes substantially to genetic variation within human populations. However, the extent to which de novo and inherited copy number variants (CNVs) underlie human disease is not well known. In this thesis, I investigate the role of de novo and inherited CNVs in a wide range of developmental abnormalities. First, I compare disease associated and apparently benign CNVs for structural differences, with the aim of identifying distinguishing features of disease causing CNVs. I identified significant enrichments of protein-coding genes, protein-coding genes associated with disease in OMIM and miRNAs amongst disease associated disease. Conversely, inherited CNVs observed in healthy individuals show depletions of these features. Following this, I employ functional enrichment approaches to identify the copy number variable genes within these de novo CNVs that contribute to the patient’s developmental abnormalities. I predict candidate genes for 143 different developmental abnormalities, with 65% of the candidate genes not having been previously associated with disease in OMIM. Through examining the distribution of these candidate genes within the patient’s CNVs, I found evidence of extensive pleiotropy and epistasis as well as a small number of simple additive effects. Finally, I extend my analyses to examine the role of inherited CNVs as the underlying cause of human developmental disorders. I implicate inherited CNVs and their overlapping copy number variable genes in the underlying causes of 45 human developmental abnormalities. Additionally, I re-examine the patients possessing both de novo CNVs and inherited CNVs using functional enrichment analyses. I reveal significant enrichments for a greater number of human developmental abnormalities when combining both the de novo and inherited CNVs, suggesting it is de novo mutations in combination with the inherited genomic background that are responsible for many instances of human developmental abnormalities.